A contribuição de Robert Wilhelm Bunsen e Gustav Robert Kirchhoff para a espectroscopia do século XIX - Pirolo, Marcelo (2010)
The dissertation approaches the works of the German researches Robert Wilhelm Bunsen and Gustav Robert Kirchhoff which have synthesized the spectral proceedings that had been used until the end of the nineteenth century. They had modified the methodology to increase a better understanding of the procedure as of the analysis of the emanated light of incandescent materials. After developing a number of experiments with Henry Roscoe on photochemistry, Bunsen had dedicated himself together with Kirchhoff to spectrum analysis. Spectroscopy is the analysis of light spectra and the way in which light interacts with matter. The light source is normally directed on a slit and is separated by the use of a prism. The image of the slit has the shape of a line to its component colors, which indicates the presence of chemical elements. Spectrometry is the technique used to assess the chemical composition and concentration of materials. This method had historically helped Bunsen and Kirchhoff finding out elements like caesium and rubidium and continued helping others to find out new elements too. For instance, helium was discovered before in solar spectrum than in earth. The spectrum analysis, enables the study in enormous distances, and consequently had transformed the Idea concerning the study of celestial bodies and finally it had provided a method for determining their chemical composition. In this dissertation we had focused on two specific works: the Photochemical Researches written by Bunsen and Roscoe and published in the Proceedings of the Royal Society of London. And Spectrum Analysis written solely by Roscoe, trying to identify the development of what would be the spectral analysis of the nineteenth century